Knowledge regarding renal stone among the nurses working in a selected specialized hospital in Bangladesh - Akter Halim, Khondoker Mahmuda; Sultana, Shirin; Khatun, Ratna; Islam, Sharmin; Muhammad, Faisal (International Journal Of Community Medicine And Public Health, 2019)
Background: Renal stone disease is a considerable burden on public health worldwide. This study aimed to assess the nurse’s knowledge regarding renal stone among the nurses working at a selected specialized hospital. Methods: A total of 120 samples were collected through purposive sampling technique. A descriptive cross-sectional study was conducted under quantitative approach. Data were collected using a structured questionnaire through face to face interview. A written informed consent was obtained from the hospital authority and nurses. Data were analysed using SPSS version 20. Results: In this study ninety percent of the respondents were female and about 43.3% of the respondents were in the age group 31-35 years. About 35.8% of the respondents had postgraduate qualification and the majority (63.3%) of the respondents had 4 years and above years of service experience. More than nine-tenths (95.8%) of the respondents mentioned that renal stone is one kind of urological disease and 75.8% of the respondents mentioned that calcium oxalate is responsible elements for formation of renal stone. About 63.3% of them mentioned pain or burning during urination as the symptoms of renal stone. 66.7% of the respondents mentioned that a patient with renal stone should be counseled on stone-specific dietary interventions. Conclusions: The findings reveal that most of the study participants had good level of knowledge regarding the renal stone. It was recommended that a special training on renal stone for nurses might be geared up to increase their level of knowledge.